Mitigating Bycatch: Novel Insights to Multidisciplinary Approaches - Squires, Dale; Ballance, Lisa T.; Dagorn, Laurent; Dutton, Peter H.; Lent, Rebecca (Frontiers in Marine Science, 2021)
Fisheries bycatch conservation and management can be analyzed and implemented through the biodiversity mitigation hierarchy using one of four basic approaches: (1) private solutions, including voluntary, moral suasion, and intrinsic motivation; (2) direct or “command-and-control” regulation starting from the fishery management authority down to the vessel; (3) incentive- or market-based to alter producer and consumer behavior and decision-making; and (4) hybrid of direct and incentive-based regulation through liability laws. Lessons can be learned from terrestrial and energy conservation, water management, forestry, and atmospheric pollution measures, such as the use of offsets, tradeable rights to externalities, and liability considerations. General bycatch conservation and management principles emerge based on a multidisciplinary approach and a wide array of private and public measures for incentivizing bycatch mitigation.